Hubungan Masa Kosong dengan Produktivitas pada Sapi Perah Friesian Holstein di Baturraden, Indonesia - A Atabany; B P Purwanto; T Toharmat; A Anggraeni (Media Peternakan, 2011)
Productivity of dairy cows not only expresed by milk yield, but also the reproductive performance. General speaking that the milk yield depends on reproductive performance and vice versa. The present study was conducted to observe the milk yield and reproductive performance of Friesian Holstein (FH) dairy cows. This study was conducted using 150 sets of weekly recording of milk yield from 50 FH cows. Milk yield was calculated by using time interval method (TIM) which was equivalent to ME 305 days. The data were analysed using polynomial regression model. Results of the study indicated that the effect of days open on milk yield had significant effect on quadratic and qubic regression model. The average days open was 138.77 days. According to the quadratic regression model, increasing days open decreased milk yield and the minimum milk yield was observed at 169 days open.